2014
DOI: 10.1371/journal.pone.0090820
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and Secretory Immunoglobulin A Response to Stress in German Shepherd Dogs

Abstract: The aim of the study was to determine whether cortisol and secretory Immunoglobulin A (sIgA) could be used as an indicator of acute stress in both young and adult dogs. Seventeen German shepherd puppies were exposed to the Puppy test (challenge test) at the age of seven weeks. This test has been routinely used to assess the future working ability of potential police dogs. In addition, ten adult females were subjected to 4 minutes of defense training under stressful conditions. Saliva was collected from the pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 46 publications
(60 reference statements)
2
32
1
Order By: Relevance
“…If combined with behavioral and other physiological measurements, the study of salivary cortisol responses is likely to yield more reliable results in reflecting animal welfare. For example, in dogs, decreases in secretary immunoglobulin A (IgA) have been linked to stressful experiences and negative correlations with cortisol were reported [ 74 , 75 , 76 ]. A stress-induced discharge of the sympathetic nervous system stimulates secretion of noradrenaline and adrenaline, accelerating heart rate [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…If combined with behavioral and other physiological measurements, the study of salivary cortisol responses is likely to yield more reliable results in reflecting animal welfare. For example, in dogs, decreases in secretary immunoglobulin A (IgA) have been linked to stressful experiences and negative correlations with cortisol were reported [ 74 , 75 , 76 ]. A stress-induced discharge of the sympathetic nervous system stimulates secretion of noradrenaline and adrenaline, accelerating heart rate [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salivary immunoglobulin A (sIgA) is a proven stress biomarker in human medicine [40]. It is known to be negatively correlated with cortisol concentration after acute stress in adult dogs but not in puppies [41]. In addition, sIgA has significant diurnal variation, which renders it less useful as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma and salivary cortisol concentrations are usually elevated 15–30 minutes after a stressor, whereas urine cortisol is more often used to provide the cumulative HPA axis activity over several hours. Salivary cortisol levels have been used as a noninvasive and easily obtained surrogate for plasma and urinary cortisol in dogs and have been measured in various environments . Salivary cortisol concentrations were found to be higher in dogs hospitalized for elective procedures versus dogs under basal conditions and were correlated with stress‐related behaviors .…”
Section: Identifying the Stressed Patientmentioning
confidence: 99%
“…Salivary cortisol concentrations were found to be higher in dogs hospitalized for elective procedures versus dogs under basal conditions and were correlated with stress‐related behaviors . Salivary cortisol concentrations were also increased in puppies and adult female dogs undergoing defense training, and in shelter dogs performing rigorous exercise, possibly indicative of stress or arousal in these animals . One study found that in dogs with separation anxiety, salivary cortisol concentrations were lower after interacting with their owners …”
Section: Identifying the Stressed Patientmentioning
confidence: 99%